Improvement of the quality for digital image watermarking based on dual ISB - Mohammed, Ghassan N.; Yasin, Azman; Zeki, Akram M. (2013)
The impeccability (quality) represent as one of the most important requirements of any watermarking system of the watermarked gray scale image. In most studies, the watermarking algorithm has to embed the watermark so that this will not affect the quality of the host data.In this study, the method concentrates on the greatest quality of the watermarked image based on Dual Intermediate Significant Bit (DISB) model.The embedding process is done by using two keys k1 and k2 where k2 > k1. The extracting process has been done after applying some types of attacks. The experimental results show that the new method improves the quality.